The Effect of Work-Life Balance and Non-Physical Work Environment on Employee Performance with Job Satisfaction as a Mediating Variable a Study of CV. Syifani Assa Mandiri - Sri Wahyuningsih; Catur Sasi Kirono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research is motivated by the problem of decreasing employee performance at CV. Syifani Assa Mandiri which resulted in a decrease in the output produced by these employees. This research aims to determine the effect of work-life balance and non-physical work environment on employee performance through job satisfaction as a mediating variable. The number of samples used was 94 CV employees. Syifani Assa Mandiri. This type of research is quantitative research. The data used in this research is primary and secondary data, namely by distributing questionnaires via Google Form to CV employees. Syifani Assa Mandiri. The application used in data processing is lisrel 8.8. The analysis used is the Structural Equation Modeling (SEM) test. The results of this research are (1) Work-Life Balance partially has a positive and significant effect on job satisfaction, (2) Non-Physical Work Environment partially has an effect on employee satisfaction, (3) Work-Life Balance partially has no effect on employee performance, (4) Non-Physical Work Environment partially influences employee performance, (5) Partially there is an influence of Job Satisfaction on employee Performance, (6) Work-Life Balance has a positive influence through job satisfaction on employee performance, (7) Non- Physical Work Environment has a positive effect on performance through job satisfaction for CV employees. Syifani Assa Mandiri.